A concept for multi-marker approaches in clinical proteomics - Mayer, Bernd (Henry Stewart Talks, 2013)
Biomarkers, Molecular processes, Disease terms, Multimarker panels, Cross-Omics, Interaction networks, Molecular disease models, Biomarker selection, Chronic disease, Patient stratification